Heart failure in erythrodermic psoriasis: a retrospective study of 225 patients - Wu, Chao; Yu, Chenyang; Yang, Yuyan; Jin, Hongzhong (Frontiers in Cardiovascular Medicine, 2023)
Purpose Erythrodermic psoriasis (EP) is a severe form of psoriasis that affects multiple organs, including the cardiovascular system. However, few studies have focused on this condition.This study is aimed to assess the prevalence and factors associated with heart failure in EP patient, and to the measure the serum concentrations of fibroblast growth factor 23 (FGF23), a potential predictor of chronic heart failure. Methods We retrospectively studied patients with EP hospitalized at Peking Union Medical College Hospital between January 2005 to October 2021. The prevalence of heart failure and associated factors was measured. In addition, peripheral blood samples were collected from 17 patients and matched with samples from eight healthy controls, and their serum concentrations of FGF23 were measured by ELISA. Results We studied 225 patients with EP, with a male: female ratio of 2.7:1 and a mean age of 47.6 ± 16.7 years. Twenty-five (11.1%) participants were diagnosed with heart failure during their hospital stay. The patients with EP and heart failure were older (58.2 years vs. 46.2 years, p = 0.001); had a higher prevalence of a history of coronary heart disease (32.0% vs. 21.5%, p < 0.001), fever (48.0% vs. 23.0%, p = 0.007), infection (56.0% vs. 35.5%, p = 0.046); higher hsCRP concentration (43.2 mg/L vs. 8.2 mg/L, p = 0.005); and higher prevalence of anemia (60.0% vs. 22.0%, p < 0.001), hypoalbuminemia (64.0% vs. 42.0%, p = 0.037), and hyperlipidemia (40.0% vs. 20.0%, p = 0.023) than those without heart failure. The serum FGF23 concentration was significantly higher in patients with EP than controls (493.1 pg/ml vs. 277.8 pg/ml, p = 0.027), and was significantly lower after treatment (395.7 pg/ml vs. 463.1 pg/ml, p = 0.022). Conclusions Clinicians should be aware of the risk of heart failure in patients with EP, and especially those of advanced age and with a history of coronary heart disease, severe systemic symptoms, high concentrations of inflammatory biomarkers, and poor nutritional status.